Predicting PICU patient survival prognosis: Pediatric Logistic Organ Dysfunction vs Pediatric Index of Mortality scores - Edwina Winiarti; Muhammad Sholeh Kosim; Mohammad Supriatna (Paediatrica Indonesiana, 2012)
Background Determining prognosis of patients using scoringsystems have been done in many pediatric intensive care units(PICU). The scoring systems frequently used are pediatric logisticorgan dy sfunction (PELOD), pediatric index of mortality (PIM)and pediatric risk of mortality (PRISM).Objective To compare the performance of PELOD and PIM scoresin predicting the prognosis of survival vs death in PICU patients.Methods A prognostic test in this prospective, cohort study wasconducted in the PICU of the Kariadi General Hospital, Semarang.PELOD and PIM calculations were performed using formulae frompreviously published articles. Statistical analyses included receiveroperating curve (ROC) characteristics to describe discriminationcapacity, sensitivity, specificity, positive predictive value, negativepredictive value and accuracy.Results Thirty-three patients fulfilling the inclusion criteria wereenrolled in the study. PELOD score for area under the ROCwas 0.87 (95% CI 0.73 to 1.0; P=0.003), while that for PIMwas 0.65 (95% CI 0.39 to 0.90; P=0.2). PELOD scores showedsensitivity 85.7% (95% CI 59.8 to 100), specificity 84.6% (95%CI 70.7 to 98.5), positive predictive value 60.0% (95% CI 29.6to 90.4) negative predictive value 95.6% (95% CI 87.3 to 100)and accuracy 84.8%. PIM scores showed sensitivity 85.7% (95%CI 59.8 to 100), specificity 50.0% (95% CI 30.8 to 69.2), positivepredictive value 31.6% (95% CI 10,7 to 52.5), negative predictivevalue 92.9% (95% CI 79.4 to 100) and accuracy 57.6%.Conclusion PELOD scoring had better specificity, positive predictivevalue, negative predictive value, accuracy and discrimination capacitythan PIM scoring for predicting the survival prognosis of patients inthe PICU. [Paediatr Indones. 2012;52:165-9].